The Blueprint of AWOS Implementation for Aviation Services at BMKG - Wardani, Duati; Sulistyo, Selo; Mustika, I Wayan (Sekolah Tinggi Teknologi Adisutjipto, 2018)
Weather is very critical for aviation. Especially regarding safety in air transportation. Badan Meteorologi, Klimatologi, dan Geofisika (BMKG) in its duties and functions provides aviation weather information, conducts the latest weather observation activities for the needs of takeoff and landing at airports. The World Meteorological Organization (WMO) has targeted automation with a target achievement in 2017. But currently in conducting the latest weather observations, BMKG still uses conventional weather observation systems even though at some airports Automated Weather Observing Systems (AWOS) have been installed. The automated weather observing system is still not fully implemented yet. This study aims to create a blueprint for the implementation of automatic weather observations for aviation services within the BMKG. Guidelines for making blueprint use the Enterprise Architecture Planning (EAP) framework. EAP defines business and architectural needs related to data, applications, and technology needed to implement automation. The final results achieved are in the form of a blueprint for the implementation of automated weather observing system for aviation services within the BMKG which can be a guide for BMKG in achieving the vision related to aviation weather services.